Pengaruh Teknik Audit Berbantuan Komputer, Kompetensi Auditor, Dan Etika Profesi Terhadap Kinerja Auditor - Alwan, Muhammad; Musyaffi, Ayatulloh Michael; Perdana, Petrolis Nusa (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
The aim of this study is to determine whether Computer-Assisted Audit Techniques, Auditor Competence, and Professional Ethics impact Auditor Performance. The study's population comprises auditors working in public accounting firms (KAP) in South Jakarta, based on the Indonesian Institute of Certified Public Accountants (IAPI) 2023 Directory as of May 22, 2023. There are 112 KAPs in South Jakarta. A sample size of 96 respondents was used, selected through Probability Sampling with the Simple Random Sampling method, measured on a Likert scale from 1 to 5. This quantitative research employs Multiple Linear Regression Analysis, processed using SPSS Version 29. The F-statistic test results show that Computer-Assisted Audit Techniques (X1), Auditor Competence (X2), and Professional Ethics (X3) collectively influence Auditor Performance (Y). The Hypothesis Test (T-test) for each X variable concerning Y indicates that Computer-Assisted Audit Techniques, Auditor Competence, and Professional Ethics positively impact Auditor Performance Compliance.